Dampening of positive affect partially accounts for the association between women’s history of child maltreatment and current depressive symptoms - Lindsey B. Stone; Alisha Sylvester (BMC Psychology)
Abstract Background Child maltreatment exerts lasting effects on emotion regulation, which in turn accounts for adult’s risk for psychopathology such as depression. In this vulnerable population, deficits in emotion regulation of negative affect are well established and include reliance on emotional suppression and rumination strategies. In contrast, alterations in the regulation of positive affect associated with child maltreatment history are less understood. We examined the role of positive rumination and dampening of positive affect, two emotion regulation strategies that may be impaired by the experience of child maltreatment and are associated with depression risk. We hypothesized that alterations in positive rumination and dampening would explain the association between women’s childmaltreatment history and heightened risk for current depressive symptoms. To determine if positive affect regulation accounts for unique variance between child maltreatment history and depression risk we controlled for brooding rumination. Methods Undergraduate women (n = 122) completed surveys on child maltreatment, depressive symptoms, and their tendency to dampen or engage in positive rumination in response to positive affect, reflecting cross-sectional data. The PROCESS macro, model 4 was run in SPSS to examine the extent to which emotion regulation strategies accounted for the association between child maltreatment history and current depressive symptoms. Results Child maltreatment history was associated with a higher tendency to dampen positive affect but was not linked with positive rumination. Dampening partially explained the link between child maltreatment and women’s current depressive symptoms. Dampening and brooding rumination each accounted for unique variance in the association between child maltreatment and depressive symptoms. Conclusions Results suggest that emotion suppression strategies among child maltreatment survivors may also extend to positive affect, with impairments in specific regulation strategies. Currently dysphoric women with a history of child maltreatment tend to dampen their positive moods and reactions to events as well as ruminate on their dysphoric moods, both tendencies accounted for unique variance in current depression risk. Longitudinal research is warranted to clarify the role of alterations in positive emotion regulations strategies in understanding how child maltreatment fosters risk for psychopathology such as depression.